A homogeneous grain-controlled ScSZ functional layer for high performance low-temperature solid oxide fuel cells. Issue 34 (14th August 2018) - Hong, Soonwook; Son, Jonghyun; Lim, Yonghyun; Yang, Hwichul; Prinz, Fritz B.; Kim, Young-Beom
Abstract : Scandia-stabilized zirconia (ScSZ) is employed as a cathodic functional layer onto yttria-stabilized zirconia based fuel cell systems for low-temperature solid oxide fuel cells. Abstract : Scandia-stabilized zirconia (ScSZ) is employed as a cathodic functional layer onto yttria-stabilized zirconia based fuel cell systems for low-temperature solid oxide fuel cells. In order to overcome the relatively poor material properties in terms of surface reaction rate, the grain structure and the degree of crystallinity of ScSZ thin films were modified by controlling the RF power during the thin-film fabrication process via sputtering. The concept of grain-controlled layers (GCLs) was applied at the cathode-electrolyte interface to enhance the surface reaction rate by catalyzing the oxygen reduction reaction. By adopting this novel concept, the thin-film fuel cell fabricated with ScSZ GCLs could achieve a peak power density of 479 mW cm −2 at 450 °C.